The Oxford handbook of structural transformation - Monga, Célestin,; Lin, Justin Yifu, 1952- (Oxford handbooks online., 2019)
'The Oxford Handbook of Structural Transformation' addresses the economics of structural transformation around the world. It deals with major themes, which include history and context, critical issues and concepts, methodological foundations, main theoretical approaches, policy issues, some illuminating country experiences of structural transformation, and important debates on the respective roles of the market and the state in that process. The historical record provides a challenge for economists to understand the success of the rising economic powers (some of them initially considered unlikely candidates for prosperity) and the stagnation or decline of others.